2022
DOI: 10.7759/cureus.32158
|View full text |Cite
|
Sign up to set email alerts
|

Septic Shock: Management and Outcomes

Abstract: The incidence rates of sepsis and septic shock as a complication have become more common over the past several decades. With this increase, sepsis remains the most common cause of intensive care unit (ICU) admissions and one of the most mortality factors, with a huge burden on healthcare facilities. Septic shock has devastating consequences on patients' lives, including organ failures and other long-term complications. Due to its dynamic clinical presentations, guidelines and tools have been established to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…In a previous study, the mortality rate was 36.5%, a similar study showed 35.2% and 39.3% mortality. 6 , 9 , 10 The lower mortality rate in our study can be due to better medical service or many patients being taken home against medical advice.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In a previous study, the mortality rate was 36.5%, a similar study showed 35.2% and 39.3% mortality. 6 , 9 , 10 The lower mortality rate in our study can be due to better medical service or many patients being taken home against medical advice.…”
Section: Discussionmentioning
confidence: 72%
“… 3 Another study showed more than half of patients were above 60 years of age. 6 Most patients 64 (23%) lie within the range of 61-70 years while a previous study showed 51-60 years of age. 3 …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Vulnerabilities to sepsis can vary by age groups, such as older adults over 65 or infants younger than 1 year old. 37,38 Differences in immune response and pathophysiology of sepsis in different age groups may have substantial impacts on clinical manifestation and requirements of different management methods, [39][40][41] dramatically influencing study design and implementation. However, the current age stratification in some trials was relatively sketchy and the dataset of such a broad age range limits the evaluation of the quality of trials encompassing infants or elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advancement of our knowledge of sepsis and improved therapeutic modalities, septic shock remains a significant contributor to mortality in intensive care units (ICUs) ( Basodan et al., 2022 ). Though extensive therapeutic studies have been conducted on animals, the results have yet to be successfully translated into human therapeutic practice.…”
Section: Introductionmentioning
confidence: 99%